America on the Ice. Antarctic Policy Issues - Klotz, Frank G. (1990)
Working together under the highly successful Antarctic Treaty of 1959, the United States and other nations have quietly and peacefully pursued exploration and scientific research in Antarctica. The treaty, however, could be subject to major revision in 1991 and possibly even elimination. It is therefore important to review U.S. national interests in anticipation of a new treaty arrangement that may necessitate modifying U.S. policy toward Antarctica. Frank Klotz examines Antarctica before the 1959 treaty, and then scrutinizes the operation of the treaty itself. In doing so, he notes three significant challenges to continued cooperation in the Antarctic have arisen despite 30 years of international cooperation. First, as the world has become more aware of dwindling natural resources, the modest discoveries in the Antarctic are attracting more attention. Second, certain nations, not signatories to the treaty, have questioned the right of the treaty members to control resource development. Third, disputes over territorial sovereignty remain to be resolved.